A vibrational spectroscopic approach to the structure and interactions of intermolecular frustrated Lewis pairs - Marques, Leandro Ramos (2023)
In this work, frustrated Lewis pairs (FLPs) were investigated aiming to understand the structure and interactions that contribute to the formation of intermolecular FLPs and the role of conventional solvents and ionic liquids (ILs) for stabilizing the Lewis pair structures. FLPs are defined as Lewis acid-base pairs that are prevented to form a classical Lewis adduct by means of steric or electronic effect, allowing them to act as prominent metal-free catalysts, mainly regarding activation of small molecules such as H2, CO2, etc. In this regard, several studies have shown that the key factor to achieve effective activate FLP products is the formation of an encounter complex. In this thesis, FLPs formed from the B(C6F5)3 Lewis acid and various phosphines as Lewis bases were prepared and studied by infrared (IR) and Raman spectroscopies along with computational calculations based on the density functional theory (DFT). In order to understand encounter complex structure in solution, vibrational techniques showed in a facile way that by probing the B(C6F5)3 Lewis acid IR bands, one can provide experimental evidence of phosphine/borane interaction through C-H···F weak hydrogen bonds, confirming that FLPs are associated in solution, though not in a specific orientation, furthermore the analysis of non-covalent interactions showed that dispersion interactions are an important stabilizing factor for the FLP association. In the formation of an encounter complex, the Mes3P/B(C6F5) (Mes=mesityl) FLP gives rise to a charge transfer band. In fact, resonance Raman (RR) spectroscopy and DFT calculations confirm that the nature of the charge transfer involves the frontier orbitals of the phosphine and borane. Although the studies on FLPs mainly involve solutions of Lewis acid-base pair in conventional solvents, some investigations using ILs as an efficient medium to stabilize FLPs have emerged. In this way, various phosphines/B(C6F5)3 Lewis pair combinations were here studied in common ILs based on the bistriflimide anion ([NTf2]¯) with imidazolium, pyrrolidinium and phosphonium cations. The association of encounter complexes could be probed and verified that imidazolium and pyrrolidinium based ILs provide more effective interaction between the Lewis species, furthermore it was found that B(C6F5)3 establishes a significant interaction with the [NTf2]¯ and still holds the association with the phosphine. These FLP/IL systems were tested in H2 activation experiments, and 1H NMR spectra confirmed the ability to split H2. Further work using ILs was based on the FLP reactivity of Lewis adducts, so by adding the B(C6F5)3 to tricyanomethanide ([TCM]¯) based ILs, it was possible to harness the potential reactivity of the adduct formed between the Lewis acid and the anion of the IL for splitting H2.